The Effect of Ease of use and Information Quality on Online Purchase Decisions at Garnier Men Official Store in Lazada - Eddy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This study aims to see the effect of ease of use and quality of information on online purchasing decisions at the Garnier men official store at Lazada. The decision to buy online is currently determined by various things, one of which is ease of use. With the ease of use of the website or application, it will make it easier for consumers to buy products. A good quality website will be easy to use and accessible to consumers. The information content on the site includes text, images, graphics, layout, sound, motion and making the right content decisions is very important for the design of related sites to be made as effectively as possible. This study uses quantitative research with the nature of explanatory research. To prove the hypothesis, the writer uses descriptive method and causal method. The results of this method can be used to prove hypotheses and causation between two or more variables in this study.The coefficient of determination between ease of use and quality of information on impulse purchases is 0.512. The regression equation is Y = 3.661 + 0.473 X1 + 0.522 X2. The results of the descriptive statistics show that the average for hedonic shopping motivation agrees. The results of descriptive statistics show that the average for ease of use, quality of information is agreed and impulse buying is agreed. The conclusion of this study is that ease of use has a positive and significant effect on purchasing decisions. Information Quality has a positive and significant effect on purchasing decisions. Ease of use and quality of information have a positive and significant influence on purchasing decisions.